Trechisibus apukhapiensis sp. n. (Coleoptera: Carabidae, Trechinae) from southeastern Andean mountains of Peru - Ruiz Tapiador, Ildefonso; Delgado Mamani, Pedro Ernesto (Institute of Life Sciences and Technologies, Daugavpils University, 2018)
A new species of ground beetle, Trechisibus (Trechisibiodes) apukhapiensis sp. n. from the Andean Mountains of southeastern Peru is described based on specimens collected in the Apu Khapia Mountain, 4 462 m. (16° 20' 41'’ S, 68° 08' 57'’ W), Puno region. This species is externally similar to T. bohorquezae and T. orophilus, yet differs specifically from them in the male genitalia.